INCLUSIVITY IN MOBILE SHOPPING APPS: AN EMPHASIS ON LEARNABILITY CHECKLISTS IN CONDUCTING A HEURISTIC EVALUATION (Journal of Digital System Development, 2023)
Studies on heuristic evaluation of mobile applications have been an emerging domain. However, existing checklists are too general and unable to clearly define the measurements for evaluating mobile shopping applications. This paper proposes suitable heuristics under the learnability measure for a checklist in conducting heuristic evaluation in supporting the inclusivity of a mobile shopping application. This study was conducted in two phases: generate the learnability measures based on heuristics and sub-heuristics from content analysis and verify the proposed heuristic evaluation checklist from the learnability measures through expert reviews. As a result, a verified Learnability checklist consisting of three heuristics was selected: recognition rather than recall, user control and freedom and match between the system and the real world. For each heuristic, suitable sub-heuristics and evaluation questions were identified. Through the learnability checklist, usability experts and analysts can consistently perform their evaluation during heuristics evaluation on other mobile shopping apps. This is to ensure that the apps have all relevant features that enhance the learning ability of their users, using the apps confidently and proficiently, providing their contentment in every usage scenario.